DESIGNÂ INOVASIÂ Â MEDIAÂ FLASHCARDÂ MAHASISWAÂ PGÂ PAUDÂ UMSURABAYAÂ UNTUKÂ MENANAMKANÂ KONSEPÂ Â MEMBILANGÂ ANGKAÂ 1Â â€“Â 9Â Â PADAÂ ANAKÂ USIAÂ DINIÂ - wahono wahono (Pedagogi : Jurnal Anak Usia Dini dan Pendidikan Anak Usia Dini, 2016)
ThisÂ  studyÂ  aimsÂ  toÂ  inspireÂ  teachersÂ  (PAUD)Â  andÂ  toÂ  gainÂ  anÂ  overviewÂ  ofÂ  theÂ  use flashcardÂ  mediaÂ  InÂ  EnhancingÂ  TheÂ  AbilityÂ  ToÂ  InstillÂ  TheÂ  ConceptÂ  OfÂ  CountingÂ  NumbersÂ  1â€9 InÂ  EarlyÂ  Childhood.Â  ResearchÂ  wasÂ  conductedÂ  onÂ  studentsÂ  TheÂ  studyÂ  programÂ  Teacher EducationÂ  EarlyÂ  ChildhoodÂ  Education,Â  UniversityÂ  ofÂ  MuhammadiyahÂ  Surabaya.Â  Experience teachesÂ  countingÂ  theÂ  mostÂ  widelyÂ  experiencedÂ  byÂ  childrenÂ  agedÂ  fiveÂ  andÂ  sixÂ  years. 90%Â  of theÂ  observationÂ  ofÂ  earlyÂ  childhoodÂ  teachersÂ  teachÂ  theÂ  conceptÂ  ofÂ  countingÂ  theÂ  numbersÂ  1â€9Â  areÂ  correct.Â  ToÂ  strengthenÂ  theÂ  child'sÂ  responses,Â  teacherÂ  invitesÂ  childrenÂ  toÂ  countÂ  the numberÂ  ofÂ  fingersÂ  togetherÂ  leftÂ  handÂ  andÂ  rightÂ  hand.Â  AfterÂ  theÂ  childrenÂ  wereÂ  askedÂ  toÂ  try yourselfÂ countingÂ theÂ fingersÂ ofÂ theirÂ leftÂ andÂ rightÂ hands. FromÂ  interviewsÂ  withÂ  teachersÂ  andÂ  parentsÂ  85%,Â  theÂ  They'veÂ  beenÂ  ableÂ  toÂ  train childrenÂ  toÂ  countÂ  theÂ  objectsÂ  thatÂ  existÂ  aroundÂ  childrenÂ  whetherÂ  atÂ  home,Â  onÂ  theÂ  road,Â  as wellÂ  asÂ  schools.Â  FromÂ  theÂ  observationsÂ  gatheredÂ  researchersÂ  foundÂ  75%Â  ofÂ  teachersÂ  and parentsÂ haveÂ not beenÂ usedÂ toÂ teachÂ countingÂ whileÂ bernyannyi,Â childrenÂ areÂ introducedÂ to theÂ  conceptÂ  ofÂ  numbers,Â  forÂ  exampleÂ  throughÂ  theÂ  songsÂ  thatÂ  matchÂ  theÂ  numbersÂ  thatÂ  will beÂ introduced,Â forÂ example:Â theÂ songÂ IÂ loveÂ mom. Â Keywords:Â  flashcardÂ media,Â countÂ theÂ numbersÂ 1â€9